Sophomoric and Skeletal-Chondroblastoma - Anubha, Bajaj (Journal of Public Health International, 2023)
A case commentary discusses a skeletal chondroblastoma with atypical features. It highlights imaging, pathology, and management considerations.
Keywords: epiphyseal; Tumour; Tumefaction; Chondroblastoma